1998
DOI: 10.1029/98jd01816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of organic aerosols formed in the α‐pinene/O3 reaction: Implications for new particle formation processes

Abstract: Abstract. The molecular composition of particle phase ozonolysis products of o•-pinene is investigated to comprehend the aerosol formation process following the VOC oxidation, focusing on an understanding of new particle formation. Two analytical approaches are applied to identify lowvolatile oxidation products in the particle phase; off-line investigations using preconcentration on Tenax TA © followed by solvent extraction and liquid chromatography/mass spectrometry as well as an on-line technique, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
237
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(244 citation statements)
references
References 30 publications
5
237
1
1
Order By: Relevance
“…However, attention is also being given to expanding the coverage of biogenic VOC to include additional terpenes and oxygenates, and a representation of gas-aerosol partitioning of the oxidised products of monoterpene degradation is being developed to assist interpretation of the formation of secondary organic aerosol observed in chamber studies (e.g. Hoffmann et al, 1997;BIOVOC, 1998;Yu et al, 1999;Jang and Kamens, 1999;Cocker et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, attention is also being given to expanding the coverage of biogenic VOC to include additional terpenes and oxygenates, and a representation of gas-aerosol partitioning of the oxidised products of monoterpene degradation is being developed to assist interpretation of the formation of secondary organic aerosol observed in chamber studies (e.g. Hoffmann et al, 1997;BIOVOC, 1998;Yu et al, 1999;Jang and Kamens, 1999;Cocker et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In the α-and β-pinene schemes, the following isomerisation reactions are included in competition with alternative decomposition routes: These reactions were included to allow the formation of the identified products pinic acid from α-and β-pinene degradation and 10-hydroxypinonic acid from α-pinene degradation (e.g. Christoffersen et al, 1998;Hoffmann et al, 1998;Jang and Kamens, 1999;Glasius et al, 2000), as described by . Reaction (25) for the complex acyl-oxy radical is assigned a probability of 80%, with the remaining 20% decomposing to eliminate CO 2 and an organic radical (in accordance with the reaction assumed for acyl-oxy radicals in general).…”
Section: Reactions Of Oxy Radical Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pathways leading to oligomer formation have been suggested, including (i) reactions of stabilized Criegee intermediates (SCI) with carboxylic acids and carbonyls, forming a-acyloxy hydroperoxides and secondary ozonides, respectively; 12,15,[18][19][20] (ii) reactions of monomer products from ozonolysis, e.g., aldol condensation, peroxyhemiacetal formation, gem-diol formation, esterification, acetal and hemiacetal formation; 13,16,18,[21][22][23][24][25][26] and (iii) formation of non-covalently bound dimer clusters of carboxylic acids. 21,[26][27][28] Pathway (i) is thought to take place in the gas phase, and pathway (ii) is suggested to occur mainly on the surface or within the bulk of SOA particles, whereas pathway (iii) may occur in both phases. Quite recently, gas phase formation of esters 17 and highly oxidized products (termed extremely low-volatility organic compounds, ELVOCs) [29][30][31][32] have been suggested in the a-pinene/O 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…A high-molecular-weight compound with a molecular weight (MW) of 358 was reported for the first time by Hoffmann et al (1998) in α-pinene/O 3 SOA using off-and online mass spectrometry (MS). With online atmospheric pressure chemical ionization (APCI) MS it was shown that this compound is formed concomitantly with two monomers, i.e., cis-pinic acid and a MW 172 compound that was tentatively identified as norpinic acid.…”
Section: Introductionmentioning
confidence: 99%